Pain during and after COVID-19 in Germany and worldwide: a narrative review of current knowledge - Meyer-Frießem, Christine H.; Gierthmühlen, Janne; Baron, Ralf; Sommer, Claudia; Üçeyler, Nurcan; Enax-Krumova, Elena K. (Pain reports, 2021)
Pain is a common symptom accompanying the coronavirus disease 2019 (COVID-19) caused by the severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2). Nonspecific discomfort such as sore throat and body ache are frequent. Parainfectious pain such as headache, myalgia, or neuropathic pain has also been reported. The latter seems to be associated with an autoimmune response or an affection of the peripheral neuromuscular system or the central nervous system because of the viral infection. Furthermore, chronic pain can be a complication of intensive care unit treatment due to COVID-19 itself (such as intensive care–acquired weakness) or of secondary diseases associated with the SARS-CoV-2 infection, including Guillain–Barré syndrome, polyneuritis, critical illness polyneuropathy, or central pain following cerebrovascular events. Data on long-lasting painful symptoms after clinically manifest COVID-19 and their consequences are lacking. In addition, preexisting chronic pain may be exacerbated by limited and disrupted health care and the psychological burden of the COVID-19 pandemic. Medical providers should be vigilant on pain during and after COVID-19.